Prediction of Academic Achievement of Vocational School Students Based on Tiktok Usage Patterns and Cognitive Styles: Multiple Linear Regression Model (Case Study: SMKS YPIS MAJU) - Amin, Khairi Syalwana (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study aimed to predict vocational high school students’ academic achievement by analyzing the influence of TikTok usage patterns and cognitive styles using a multiple linear regression model. The research was conducted at SMKS YPIS Maju Binjai with a sample of 100 students selected through purposive sampling. Data were obtained through questionnaires on TikTok usage patterns and cognitive styles, as well as students’ academic records. TikTok usage (X1) was measured by frequency, duration, and its impact on study habits, while cognitive style (X2) was measured based on visual, verbal, and mixed learning preferences. Academic achievement (Y) was represented by students’ average report card scores. The regression analysis produced the equation Ŷ = 85.869 +(- 0.3495X1) + (0.1993X2). The results showed that TikTok usage had a significant negative effect on academic achievement, whereas cognitive style had a significant positive effect. The model demonstrated good predictive accuracy with R² = 0.392, MAE = 1.77, MSE = 5.26, RMSE = 2.29, and MAPE = 2.16%. This study contributes by integrating social media usage patterns and cognitive factors to predict students’ academic achievement and provides practical insights for educators in guiding students to balance social media use with academic learning.